Non-pharmacological behavioral management techniques in pediatric dentistry (Research, Society and Development, 2022)
It is common knowledge among dental professionals that the relationship is the main difference between the treatment of children and adults within the dental office. This relationship is based on methodologies considered essential in the literature for behavioral control. To make use of the main behavior control techniques in the pediatric dentistry clinic, professionals must have sufficient knowledge and background to discern among the techniques and characteristics of each patient. The objective of this work is, through a literature review, to describe the non-pharmacological behavioral management techniques used in pediatric dentistry. Articles published between 2012 and 2022 related to non-pharmacological behavioral management techniques in pediatric dentistry were analyzed, as well as their importance for the biopsychosocial development of children. Articles were selected from the aforementioned Pubmed, Bireme, SciELO and LILACS databases. After reading and detailed analysis, 18 articles were chosen, which make up the entire bibliographic body of this article and contribute to the scientific community. Conclusion: Non-pharmacological behavioral management techniques are described in the literature as efficient strategies that aim to alleviate children's fear and insecurity regarding dental care. For this, it is necessary that the professionals involved in conducting the service have knowledge about child behavior, child psychology and master techniques that help in adult-child interaction.